법과 은유 -법시학의 가능성을 모색하면서 - 김연미(Yeon Mi Kim) (Pŏpch'ŏrhak yŏn'gu, 2014)
이 글은 우선 시적 어법으로서 은유에 대한 서양법철학의 역사를 부분적으로 고찰할 것이고, 그 다음 인지체계를 형성하는 은유의 개념체계를 법적 관념에 적용해볼 것이다. 은유에 대한 법적 고찰로부터 필자는 시적 정의가 지니는 상상력의 구조가 법해석의 성격을 ‘유추적 해석’이 아니라 ‘은유적 이해’라는 정합적 성격을 제공한다는 결론에 이른다. 법은 해석의 산물이 아니라 은유(metaphor)의 산물이다. 특히 법이 은유의 산물이라는 점에서 법은 전통적인 시학과 분기되는 곳에서 다시 시적 정의와 법적 정의의 관계를 고찰할 필요성이 제기된다. 전통적으로 은유는 시적 어법이었기 때문에 언어적 비정상성 내지 진리를 왜곡한다고 생각되어 왔다. 레이코프와 존슨(Lakoff & Johnson)의 현대 인지학(cognitivism)은 객관주의(objectivism)적 의미론을 거부하고, 은유의 개념체계를 통해 우리의 사유체계를 새롭게 했다. 우리의 사유체계는 대부분 체화된 마음(embodied mind)의 상상력의 구조를 띠고 있으며, 은유는 주요한 상상력의 구조 중 하나이다. 은유는 법적 판단에 있어서 공적 상상력의 구조를 띤다. 시인에게 필요한 리듬과 말의 중요성은 법관이나 입법가에게도 필요하다. 공동체의 리듬을 읽어내기 위한 공적 상상력의 구조는 체험주의(experientialism)에 바탕한다. [법시학]은 법철학의 은유적 표현이다. 이 글은 [법은 시이다] 은유를 체험주의은유이론에 바탕하여 시의 이해를 근원영역(source domain)으로 하고, 법을 목표영역(target domain)으로 하여 교차영역간 사상(cross-domain mapping)을 통해 법을 이해하는 법철학적 작업이다. 이 글에서 필자는 헌법 제10조에서 제37조1항에 이르는 기본권목록을 체험주의은유이론에 입각하여 분석하였다. [인간존엄성]과 [권리]의 공간적, 지향적 및 존재론적인 개념적 은유들을 통해 [인간존엄성]의 보편성논제를 새롭게 조명하였다. This study starts from the relation between poetic justice and legal justice which bases on the brief history of metaphor. Plato did not accept a poetic justice in his ideal Republic. But Aristotle precisely studied a poetic justice as a metaphor. Legal analogical interpretation belongs to Aristotle’s metaphor theory. The first turning point occured in Coleridge’s Potics. It is important to observe his poetic imagination that offered Richards and Lakoff & M. Johnson’s experientialism as the second turning point, the metaphorical thought. Poetic imagination focused upon the unity of the object and the subject, or an universal and a particular. The cross-domain mapping among the different species, such as law and poetry, produces metaphorical inference. The greater part of this study depends on Lakoff & Johnson’s cognitivism. The metaphorical imagination, such as poetic imagination, also needs for the process in Judge’s decision. [Law is Poetry] is a metaphor for Legal Poetics as a construction supporting legal philosophy. I think that legal decision as well as law-making should meet public imagination and rhythm. I apply metaphorical concepts (i.e. structural, ontological, oriental metaphor) to [human dignity] and constitutional rights of the Republic of Korea (§10-§37). If human dignity and value according to metaphorical inference is a target domain, then rights is a sources domain. Also if rights is a target domain, then the history about the experience of human violationand infringements has been a sources domain. All embodied concrete experiences in the dimension of individual, also social and cultural dimension base on a legal prototypical categorization. After all, most of laws are not the product of an interpretation but of a metaphor. KCI Citation Count: 3